Thirteenth child - Wrede, Patricia C., 1953- (New York : Scholastic Press, 2009)
Eighteen-year-old Eff must finally get over believing she is bad luck and accept that her special training in Aphrikan magic, and being the twin of the seventh son of a seventh son, give her extraordinary power to combat magical creatures that threaten settlements on the western frontier.
A Junior Library Guild selection
Keywords: Magic -- Juvenile fiction; Schools -- Juvenile fiction; Frontier and pioneer life -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Magic -- Fiction; Schools -- Fiction; Frontier and pioneer life -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Fantasy